Violanta opera in one act - Korngold, Erich Wolfgang 1897-1957 (Dynamic Srl, 2020)
Erich Wolfgang Korngold was a child prodigy whose early genius was recognized and admired by the likes of Gustav Mahler and Giacomo Puccini. His musical style, deeply affected by music for the theatre, possessed great lyrical breadth; he managed to develop his own voice by blending all the different influences he absorbed in Vienna during his studies. Teatro Regio di Torino has contributed to the rediscovery of this precious one-act opera by staging its Italian premiere
Recorded at: Teatro Regio Torino, 21st and 23rd January 2020
First Italian performance
World permière on video
Keywords: Film; DVD-Video